2016
DOI: 10.1155/2016/6402942
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stress Regulation on Neural Plasticity in Pain Chronification

Abstract: Pain, especially chronic pain, is one of the most common clinical symptoms and has been considered as a worldwide healthcare problem. The transition from acute to chronic pain is accompanied by a chain of alterations in physiology, pathology, and psychology. Increasing clinical studies and complementary animal models have elucidated effects of stress regulation on the pain chronification via investigating activations of the hypothalamic-pituitary-adrenal (HPA) axis and changes in some crucial brain regions, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 110 publications
(130 reference statements)
2
41
0
Order By: Relevance
“…Functional blockade of glutamatergic neurons in the unilateral LHb was enough to alleviate pT-ION-induced anxiety-like behaviors but not allodynia, as was rescuing the pT-ION-induced downregulation of Tacr3, a gene enriched in the calcium signaling pathway. The anterior cingulate cortex (ACC), prefrontal cortex (PFC), and hippocampus were reported to be related to the induction of negative emotion [25]. Here we found that the downregulation of Tacr3 occurred only in the LHb and not in the ACC, PFC, or hippocampus.…”
Section: Introductionmentioning
confidence: 52%
“…Functional blockade of glutamatergic neurons in the unilateral LHb was enough to alleviate pT-ION-induced anxiety-like behaviors but not allodynia, as was rescuing the pT-ION-induced downregulation of Tacr3, a gene enriched in the calcium signaling pathway. The anterior cingulate cortex (ACC), prefrontal cortex (PFC), and hippocampus were reported to be related to the induction of negative emotion [25]. Here we found that the downregulation of Tacr3 occurred only in the LHb and not in the ACC, PFC, or hippocampus.…”
Section: Introductionmentioning
confidence: 52%
“…Nociceptive signals are moderated at the level of the spinal cord by descending modulatory neural pathways, which may either facilitate or inhibit their transmission. 21 Chronic stress and chronic pain share neural circuits that operate in the amygdala, the hippocampus and the prefrontal cortex 23 ; and cortisol plays an essential role in the prefrontal cortex-dependent regulation of the hypothalamic-pituitary-adrenal (HPA) axis and in the processing of emotion-related information by the amygdala. 8 It appears that on one hand, long-term exposure to psychosocial stressors brings about an increase in neuronal dendritic arborisation and axonal connections in the amygdala with the upregulation of activity of neuronal pathways for both nociception and stress; and on the other hand, a decrease in dendritic arborisation and axonal connections in the prefrontal cortex and the hippocampus with downregulation of activity of nociceptive and stress inhibitory pathways.…”
Section: Chronic Painmentioning
confidence: 99%
“…While studies constructed a bridge between excessive release of PGs in the menstruation phase and dysmenorrheic pain in PD patients, there is mounting evidence that PD patients are hypersensitive to experimental pain not only when they are experiencing menstrual pain, but also during the pain‐free phase of the menstrual cycle [Iacovides et al, ]. Researchers pointed out that a vicious cycle of painful stimuli caused by uterine cramps may increase nociceptive‐related neuronal input in the brain [Iacovides et al, ; Li and Hu, ], which was associated with structural changes and functional reorganization in pain‐related brain networks [Bajaj et al, ]. This could be a viable explanation for the enhanced pain sensitivity even in the phase when PD patients are not experiencing menstrual pain [Iacovides et al, ; Vincent et al, ].…”
Section: Introductionmentioning
confidence: 99%